Fast Dissolving/Disintegrating Dosage Forms of Natural Active Compounds and Alternative Medicines - Singh, Anupama; Kharb, Vandana; Saharan, Vikas A. (Recent Patents on Drug Delivery & Formulation, 2020)
Fast Dissolving/Disintegrating Dosage Forms (FDDFs) are a group of dosage forms which dissolve or disintegrate quickly, leading to fast distribution of active ingredients at the site of administration; thereby providing ease of oral ingestion of solid unit dosage forms and have the potential to enhance transmucosal absorption. With time, the use of FDDFs in alternative systems has significantly increased. Homeopathic systems and traditional Chinese medicine have embraced FDDFs for the delivery of active compounds. Most of the patents in this area are from China or by the Chinese innovators. In Europe and US, FDDFs have been extensively studied for the delivery of natural active compounds. It was fascinating to know that some new dosage forms and new routes of delivering active compounds are also making their way to the family of FDDFs. The dose of active compound, size of dosage forms, standardization of extracts, polyherbal mixtures, stability of active compounds, safety, efficacy and pharmacokinetics are challenging issues for developing FDDF herbal formulations or phytopharmaceuticals.
Keywords: Orodispersible